Raising the Buddha’s Hand: Illusory Ownership in the Experience of Identification with a Supernatural Agent in Deity Yoga - Szymanek, Piotr; Ciołkosz, Matylda (Journal for the Cognitive Science of Religion, 2024)
Deity yoga is a practice found in Tibetan Buddhism involving visualizations that have the normative goal of “becoming one” with a supernatural being. During the practice, practitioners report experiencing that their own body transforms into the body of the deity. This paper offers a potential cognitive explanation of how such an experience is possible. Applying findings from cognitive science on the phenomenon of illusory ownership, we argue that the practice of deity yoga has the necessary means to cause an experience analogous to the famous “rubber hand illusion” in which one misattributes their ownership to a fake hand. In this paper, we 1) introduce deity yoga practice and its key aspects; 2) discuss illusory ownership and its explanation embedded in a predictive processing framework; 3) argue that visualization in deity yoga may induce the experience of illusory ownership; and 4) conclude with a short discussion of the hypothesis’ limitations and of ways to test our hypothesis. Overall, the paper suggests how the practice of visualization in deity yoga may lead to an experience of a transfer of identity onto an imagined supernatural agent.